Electron‐Scale Magnetic Structure Observed Adjacent to an Electron Diffusion Region at the Dayside Magnetopause. Issue 12 (17th December 2019) - Hoilijoki, S.; Ergun, R. E.; Schwartz, S. J.; Eriksson, S.; Wilder, F. D.; Webster, J. M.; Ahmadi, N.; Le Contel, O.; Burch, J. L.; Torbert, R. B.; Strangeway, R. J.; Giles, B. L.
Abstract: In this paper, we present observations made by the Magnetospheric Multiscale (MMS) mission of a small‐scale magnetic structure adjacent to a reconnecting current sheet at the dayside magnetopause. While MMS crosses the current sheet, it observes signatures of an electron diffusion region (EDR), including crescent shaped electron velocity distribution functions. Right after the EDR crossing, all spacecraft encounter an electron‐scale magnetic structure that can roughly be divided into two parts: a force‐free flux rope‐like part and a nonforce‐free magnetic enhancement. Within the leading force‐free part of the structure, the magnetic field component normal to the current sheet exhibits a bipolar signature, suggesting that the structure is flux rope‐like. In the trailing edge of the bipolar signature, three spacecraft observe a magnetic enhancement that has an amplitude almost twice the ambient magnetic field. The magnetic peak adjacent to an EDR can be associated with an electron vortex, where the perpendicular current is carried by E ×B drifting electrons. The structure is advected tailward along the magnetopause while in the plasma frame, it propagates upstream suggesting that this reconnection event is highly three‐dimensional. Fluctuations in the plasma density and magnetic field and large peaks in the parallel electric field observed on the magnetospheric side of the EDR suggest that the current sheet is corrugated due to an electromagnetic drift instability. This or another instability of a thin reconnecting current sheet (e.g., tearing) is a likely cause of the formation of the observed magnetic structure. Key Points: MMS observed a complex electron‐scale magnetic structure adjacent to dayside electron diffusion region Magnetic structure consists of a force‐free flux rope‐like part and a non‐force‐free magnetic enhancement supported by an electron vortex Structure propagates upstream in the plasma frame suggesting that it is formed due to an instability of a thin current sheet